First pilot case-control interventional study using autologous extracellular vesicles to treat chronic venous ulcers unresponsive to conventional treatments. (April 2023) - Gibello, Lorenzo; D'Antico, Sergio; Salafia, Marika; Senetta, Rebecca; Pomatto, Margherita Alba Carlotta; Orlando, Giulia; Sarcinella, Alessandro; Lopatina, Tatiana; Quaglino, Pietro; Lorenzi, Marco; Verzini, Fabio; Camussi, Giovanni; et al.
Abstract: Current therapeutic approaches for chronic venous ulcers (CVUs) still require evidence of effectiveness. Diverse sources of extracellular vesicles (EVs) have been proposed for tissue regeneration, however the lack of potency tests, to predict in-vivo effectiveness, and a reliable scalability have delayed their clinical application. This study aimed to investigate whether autologous serum-derived EVs (s-EVs), recovered from patients with CVUs, may be a proper therapeutic approach to improve the healing process. A pilot case-control interventional study (CS2/1095/0090491) has been designed and s-EVs recovered from patients. Patient eligibility included two or more distinct chronic lesions in the same limb with 11 months as median persistence of active ulcer before enrollment. Patients were treated three times a week, for 2 weeks. Qualitative CVU analysis demonstrated that s-EVs-treated lesions displayed a higher percentage of granulation tissue compared to the control group (Sham) (s-EVs 3 out of 5: 75–100 % vs Sham: none), further confirmed at day 30. s-EVs-treated lesions also displayed higher sloughy tissue reduction at the end of treatment even increased at day 30. Additionally, s-EV treatment led to a median surface reduction of 151 mm 2 compared to 84 mm 2 in the Sham group, difference even more evident at day 30 (s-EVs 385 mm 2 vs Sham 106 mm 2 p = 0.004 ). Consistent with the enrichment of transforming growth factor-β1 in s-EVs, histological analyses showed a regenerative tissue with an increase in microvascular proliferation areas. This study first demonstrates the clinical effectiveness of autologous s-EVs in promoting the healing process of CVUs unresponsive to conventional treatments. Graphical Abstract: ga1